2008
DOI: 10.1128/jvi.01016-08
|View full text |Cite
|
Sign up to set email alerts
|

Human Endogenous Retrovirus Family HERV-K(HML-2) RNA Transcripts Are Selectively Packaged into Retroviral Particles Produced by the Human Germ Cell Tumor Line Tera-1 and Originate Mainly from a Provirus on Chromosome 22q11.21

Abstract: The human germ cell tumor line Tera-1 produces retroviral particles which are encoded by the human endogenous retrovirus family HERV-K(HML-2). We show here, by quantitative reverse transcriptase PCR, that HML-2 gag and env RNA transcripts are selectively packaged into Tera-1 retroviral particles, whereas RNAs from cellular housekeeping genes and from other HERV families (HERV-H and HERV-W) are nonselectively copackaged. Assignment of cloned HML-2 gag and env cDNAs from Tera-1 retroviral particles to individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 49 publications
4
77
0
2
Order By: Relevance
“…The levels of gapdh transcripts decreased in IP samples compared to those of the raw supernatant. The residual low levels of gapdh in IP samples is expected, as this has been reported in studies of other retroviruses (32,(69)(70)(71)(72)(73)(74)(75)(76), which can package different nonviral RNA sequences at low levels. Further, enrichment of HK2 gag and Bogota neo transcripts found in HK2 VLPs was 5 to 20 times greater than that of gapdh transcripts (Fig.…”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…The levels of gapdh transcripts decreased in IP samples compared to those of the raw supernatant. The residual low levels of gapdh in IP samples is expected, as this has been reported in studies of other retroviruses (32,(69)(70)(71)(72)(73)(74)(75)(76), which can package different nonviral RNA sequences at low levels. Further, enrichment of HK2 gag and Bogota neo transcripts found in HK2 VLPs was 5 to 20 times greater than that of gapdh transcripts (Fig.…”
Section: Resultsmentioning
confidence: 55%
“…3C). In order to determine the packaging efficiency of these transcripts into the pelleted retroviral VLPs, we compared the levels of transcripts found in the pelleted retroviral VLPs to the ones found in the cellular RNA using a previously validated methodology (32,77,78). Of these transcripts, HK2 genes and Bogota HK2 appear to be the most abundant retroviral transcripts in NCCIT cellular RNA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…obtained here with a cDNA clone from a MGCT show that K101 can contribute to production of these particles. Others have shown that K101 and K108 are transcribed in MGCTs (23,54), and RNAs from these proviruses are packaged into particles produced in MGCTs (54). HERV-K particle production has also been reported to occur in normal human placenta (21,29,58), and K101, K108, and K109 are candidates for encoding those particles.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence indicates that multiple sclerosis-related virus (MSRV) pol derived from HERV-W and HERV-K is expressed in the brain tissues of MS patients and is associated with the cause of MS (Johnston et al, 2001;Antony et al, 2011). As described above, HERVs play a role in the development of malignant transformation or tumor growth via the production of HERVencoded oncogenic proteins such as Rec/Np9, and insertional mutation disturb binding of tumor suppressors like P53 and tissue specific expression alteration (Ruprecht et al, 2008;Belancio et al, 2010). HERV-K has been detected in germ cell tumors and in primary or metastatic human melanomas (Gallus et al, 2010).…”
Section: Human Diseases and Retroelementsmentioning
confidence: 99%